Antiferromagnetic half-skyrmions and bimerons at room temperature - Radaelli, P (University of Oxford, 2021)
The datasets included herein contain experimental results (X-ray absorption, dichroic photoemission electron microscopy, diffraction, magnetometry etc.) and related analysis for the investigation of antiferromagnetic topological textures. The processes used in the obtaining, reducing and analysing the datasets can be found in the Methods and Supplementary Information sections of the published manuscript.